Argostemma wardii (Rubiaceae), a new species from Ayeyarwady Region, Myanmar - Quan, Dong-Li; Xie, Xing-Chi; Yang, Bin; Swe, Yadanar; Htwe, Kaung Myat; Tan, Yun-Hong (Phytotaxa, 2025)
Argostemma wardii Y.H.Tan & D.L.Quan, a new species of Rubiaceae is described and illustrated from Ayeyarwady Region, southern Myanmar. This species is closely similar to A. kurzii but can be distinguished by its typically having 2-paired leaves that are thinly papery and spatulate, lanceolate, or elliptic in shape, with bases that are attenuate, cuneate, or asymmetrical. Additionally, A. wardii has larger stipules (5–15 × 10–30 mm vs. 1 × 2–5 mm), fewer inflorescences (1 or rarely 2 vs. 1–4), shorter peduncles (1.5–6.5 cm vs. 4–12 cm), a fleshy calyx (vs. chartaceous), subtle corolla venation (vs. conspicuous), and larger bracts (2–7 × 5–12.5 mm vs. 2–3.5 × 3–5 mm) and corollas (2 × 4–4.5 mm vs. 1.5 × 2–2.5 mm), along with longer corolla tubes (0.5–1 mm vs. 0.4–0.6 mm) and anthers (2–2.5 mm vs. 1 mm).